2012
DOI: 10.1037/a0023479
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and mental health: Changes in religious beliefs, complicated grief, posttraumatic stress disorder, and major depression following the September 11, 2001 attacks.

Abstract: This cross-sectional retrospective study examined self-perceived changes in importance of religious beliefs (RBs) following the attacks of September 11, 2001, and assessed their associations with complicated grief (CG), posttraumatic stress disorder (PTSD), and major depressive disorder (MDD). Data were collected from 608 participants 2.5 to 3.5 years after the attacks. Whereas the majority of the participants reported no change in importance of RBs, 11% reported increased importance and 10% reported decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 51 publications
2
33
0
Order By: Relevance
“…Consistent with findings from nonmilitary samples (Falsetti, Resick, & Davis, 2003;Seirmarco et al, 2012), research also suggests that military traumas might disrupt spirituality and that negative changes in this domain contribute to veterans' decisions to seek treatment in many cases. When compared to demographically-matched counterparts from the community, found that Vietnam and Iraq/Afghanistan veterans presenting for PTSD treatment had lower scores on adaptive aspects of spirituality while simultaneously endorsing greater forgiveness problems and negative religious coping.…”
supporting
confidence: 61%
“…Consistent with findings from nonmilitary samples (Falsetti, Resick, & Davis, 2003;Seirmarco et al, 2012), research also suggests that military traumas might disrupt spirituality and that negative changes in this domain contribute to veterans' decisions to seek treatment in many cases. When compared to demographically-matched counterparts from the community, found that Vietnam and Iraq/Afghanistan veterans presenting for PTSD treatment had lower scores on adaptive aspects of spirituality while simultaneously endorsing greater forgiveness problems and negative religious coping.…”
supporting
confidence: 61%
“…Other research paints a more complex picture, suggesting that religious coping offers no special advantages over non-religious coping [57], and that recollected declines in the importance of religious belief are associated with poorer psychological well-being [69]. Longitudinal NZAVS survey data taken before and after the Christchurch earthquakes enabled us to examine change in faith and subjective well-being in the wake of a natural disaster.…”
Section: Discussionmentioning
confidence: 99%
“…Recall that Seirmarco and colleauges observed declines in the reported importance of religious beliefs several years after September 11 attacks were associated with reported severity of personal loss from the tragedy [69]. In the aftermath of a horrific and deadly earthquake, it is plausible that those religious people who experienced the greatest losses to subjective well-being were overwhelmingly challenged in their faith, from excessive existential concerns and incongruities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For those that suffer a decrease in their religious affiliation due to the shattering effects of trauma, an increased susceptibility to psychological distress is often found. In a survey of 608 individuals who had lost a friend or loved one in the September 11, 2001, terrorist attacks on the twin towers, Seirmarco et al (2012) found that the 11% of respondents that self-reported a decrease in their religious beliefs were almost three times more likely to screen positive for complex grief, two and a half times more likely to have major depressive disorder, and two times more likely to have posttraumatic stress disorder.…”
Section: Empirical Connections Between Trauma and Spiritualitymentioning
confidence: 99%